Actualizing AI Affordances in ELT Practicum: Mediating Factors in Pre-Service Teachers’ Pedagogical Use - Alya Rosa Salsabilla; Endang Setyaningsih (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The rapid adoption of artificial intelligence (AI) in English language teaching (ELT) has prompted growing interest in its pedagogical potential. However, existing studies on AI in ELT have largely focused on teachers’ perceptions of AI benefits and challenges, with limited attention to the mechanisms through which AI affordances are actualized in authentic teaching practicum contexts. Grounded in affordance theory, this qualitative case study investigates how and under what conditions pre-service English teachers actualize AI affordances during teaching practicum. Data were collected through a questionnaire (n = 30) and in-depth semi-structured interviews with three purposively selected pre-service teachers. Thematic analysis revealed that AI’s enabling affordances were actualized when pre-service teachers critically evaluated and adapted AI-generated outputs through pedagogical knowledge, content knowledge, ease of use, and prompt literacy. Conversely, limitations in pedagogical knowledge, particularly in articulating pedagogical intent through prompts and ethical uncertainty, constrained the actualization of AI’s enabling affordances. The findings suggest that AI’s pedagogical value does not reside in the technology itself but emerges through teachers’ situated perceptions, knowledge, and actions. This study highlights the importance of explicit pedagogical guidance in teacher education to support meaningful AI integration.